Effect of sintering temperature on the synthesis of LiZnMnFe microwave ceramics with controllable electro/magnetic properties. Issue 21 (1st November 2021) - Martinson, K.D.; Ivanov, A.A.; Panteleev, I.B.; Popkov, V.I.
Abstract: Self-propagating high-temperature (SPHT) assisted method was successfully used to obtain soft magnetic ceramics based on the nanostructured powder of multicomponent lithium ferrite Li0·45 Zn0·08 Mn0·06 Fe2·41 O4 . The influence of various temperature modes of sintering (900–1075 °C) on the microstructure, morphology, phase composition, and magnetic and electromagnetic properties of the initial powder and final ceramic products was analyzed in detail by methods of scanning electron microscopy, transmission electron microscopy, energy-dispersive and atomic absorption spectroscopy, thermogravimetry, calorimetry, X-ray diffractometry, induction magnetometry and measurement of electromagnetic parameters. It was shown that the particle size of the initial powder is 40 nm and depending on the sintering modes, it is possible to obtain lithium-zinc-manganese ferrite ceramics with an average grain size from 0.35 to 2.96 μm and porosity varying from 3.8 to 23.3%. The coercive force, residual induction, and saturation induction of the obtained samples were 51.3–816.6 A/m, 761.40–2131.30 G, and 1234.28–3431.71 G, respectively. It was found that the sample sintered at a temperature of 1075 °C for 8 h demonstrated the most pronounced soft magnetic behavior. The electromagnetic characteristics of the obtained samples also depended on the selected sintering mode and reached their maximum for ceramics sintered at a temperature of 1075 °C ( ϵ'  = 11.52; ϵ"  = 6.32⸱10 −3 ; tan δ ϵ  = 5.49⸱10 −4 ; Δ H  = 280 Oe; Δ H k  = 1.87 Oe).